The Influence of Location, Price and Product Quality on Repurchase Intention on Food Stall Empek-Empek Cinata at Ngabang, Landak Regency - Gusti Firliyansyah; Samsuddin Samsuddin (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the influence of Location, Price, and Product Quality on Repurchase Intention at Warung Makan Empek-Empek Cinata in Ngabang, Landak Regency. The research employs a quantitative approach with an associative design. The sampling technique used is purposive sampling. The number of respondents consists of 100 consumers who meet the criteria of purposive sampling. Data analysis is conducted using multiple linear regression analysis with the assistance of SPSS version 25 software, supported by validity testing, reliability testing, and classical assumption testing. The results show that partially, Location has a positive and significant effect on repurchase intention, with a calculated t-value of 2.265 t-table value of 1.661. Similarly, Price has a positive and significant effect on repurchase intention with a calculated t-value of 2.473 t-table value of 1.661, and Product Quality also has a significant effect on repurchase intention with a calculated t-value of 2.834 t-table value of 1.661. Simultaneously, Location, Price, and Product Quality have a significant effect on repurchase intention (p 0.001), with a coefficient of determination (R²) value of 0.395. These findings indicate that Location, Price, and Product Quality are able to explain 39.5% of the contribution to repurchase intention, while the remaining percentage is influenced by other factors outside the research model.